The state of corporate sustainability reporting in India: Evidence from environmentally sensitive industries. (24th December 2021) - Kumar, Kishore; Kumari, Ranjita; Kumar, Rakesh
Abstract: The purpose of this study is to explore the extent and nature of sustainability disclosure practices of companies from environmentally sensitive industries in India. It further investigates the influence of potential determinants on sustainability information disclosure of the companies. The study analyzed the data of 57 energy and mining companies included in NIFTY500 index at National Stock Exchange of India (NSE) for the period 2016 to 2019. In the present study, environment, social, and governance (ESG) parameters were considered to measure the corporate sustainability disclosure practices. Panel data analysis was conducted to investigate the impact of possible determinants on sustainability reporting. The results indicate that variables, such as firm size, market capitalization, and a standalone sustainability reporting, are positively associated with the sustainability information disclosure of companies. The finding also suggests that policymakers should promote a standalone sustainability reporting based on Global Reporting Initiative (GRI) standards and also broaden the existing scope of business responsibility reporting in India. Overall findings should help the policymakers and regulators to assess and advance the disclosure reforms to improve sustainability reporting in India.